Enhancing patient safety: leveraging artificial intelligence-powered electronic medical records for effective drug-drug interaction nudge in real-world prescribing practices - Jayanthy, G.; Majumdar, Arnab; Kaloo, Supriya; Shah, Snehal (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Concurrent prescriptions of various medications may lead to unfavorable and unanticipated potential drug-drug interactions. Hence, the elimination of drug-drug interactions is a key aspect of delivering a coherent treatment regime. In response to this concern, HealthPlix, one of India's largest AI-powered electronic medical record providers, introduced a drug-drug interaction nudge feature in June 2022, providing a proactive solution for physicians to address potential interactions between incompatible drugs. This study aimed to elucidate the role of electronic medical records in identifying and managing drug interactions and the advantages of interaction nudges for doctors in prescribing appropriate medications. Methods: An observational retrospective study was conducted using data obtained from HealthPlix, containing two or more drugs, written for patients older than 18 years. Results: In an average of 1.9 million patient visits analyzed, the interaction visits were observed to be 1.2 million. An average of 185,745 interactions were observed during the study period. For all observed interactions, an average of 72,383 molecules were removed. These results provide insights into the efficiency of HealthPlix in abrogating interactions and illustrate the tangible benefits of nudges in modifying prescription practices. Conclusions: The above results illustrate the effectiveness of drug-drug interaction nudges as a clinical decision support tool integrated into HealthPlix, marking a significant advancement in Indian healthcare. This unique feature contributes to reducing the frequency of potent drug interactions, showcasing its potential to enhance patient safety and improve the quality of healthcare delivery.